Sharp Increase in rapid intensification of Arabian Sea tropical cyclones over the past decade - Xiaojing Li; Yi Li; Youmin Tang (Communications Earth & Environment)
Abstract The Arabian Sea has experienced a sharp increase in extremely severe tropical cyclones over the past decade, yet the drivers behind this trend remain unclear. Here we examined rapid intensification - a critical process enhancing tropical cyclone intensity - using multi-source observations and reanalysis data. We find that both the frequency of rapid intensification events and number of tropical cyclones undergoing them have doubled since 2013, accompanied by southwestward and northward expansion of rapid intensification-prone regions. Machine learning analysis identifies rising sea surface temperatures and enhanced 850 hPa vorticity as key factors behind this surge. Future projections indicate further increases in these factors, suggesting more frequent rapid intensification events and consequent heightened cyclone risks in this region. These findings highlight the critical role of large-scale oceanic and atmospheric changes in shaping tropical cyclone behavior and emphasize the urgent need for targeted adaptation strategies.